A hybrid key schedule algorithm based on blum blum shub generator and chaotic systems - Cakil, Ahmet Can; Özkaynak, Fatih (Institute of Electrical and Electronics Engineers Inc., 2021)
Encryption algorithms are now becoming an important part of our daily lives. Therefore, being able to design effective encryption algorithms has become a hot research topic in computer science studies. An integral component of an encryption algorithm is key scheduling algorithms. In this study, a new approach that can be used as a key scheduling algorithm is proposed. The proposed approach has an innovative aspect that combines the advantages of deterministic and true random number generators. It is thought that this new hybrid approach, both successfully providing statistical analysis and having an unpredictable structure, will be a reason for preference for possible practical applications to be designed in the future. © 2021 IEEE.
16th IEEE International Conference on Computer Science and Information Technologies, CSIT 2021 -- 22 September 2021 through 25 September 2021 -- Lviv -- 175940
Keywords: Blum Blum Shub generetor; Chaotic systems; Cryptography; Key planning algorithm; Random number generator